Self‐assembling amphiphilic PEGylated block copolymers obtained through RAFT polymerization for drug‐delivery applications. Issue 11 (20th November 2015) - Colombo, Claudio; Gatti, Simone; Ferrari, Raffaele; Casalini, Tommaso; Cuccato, Danilo; Morosi, Lavinia; Zucchetti, Massimo; Moscatelli, Davide
ABSTRACT: In this work, ring‐opening polymerization and reversible addition‐fragmentation chain transfer polymerization (RAFT) have been employed for the production of block copolymers where the backbone is brushed with poly(ethylene glycol) (PEG) and polyester chains. Because of their amphiphilic properties, they are able to self‐assemble in water, forming micelles. Molecular dynamics simulations have been accomplished to study the behavior of the copolymer single chain in water, and the self‐assembly properties have been characterized and correlated to the copolymer structure in terms of critical micellar concentration and particle size. As a proof of their flexibility, these materials have been employed for the production of polymer–lipid hybrid nanoparticles with tunable dimensions (from 120 to 260 nm) adopted for the controlled release of anticancer compounds (paclitaxel and curcumin). © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43084. Abstract :